Heritage and Hospitality: A Tourist Loyalty Model in a Historic Hotel of Inna Group Bali - I Gusti Kade Heryadi Angligan; I Nyoman Sunarta; Anak Agung Putu Agung Suryawan Wiranatha; I Made Adikampana (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
Bali's tourism sector is facing increasing competition, underscoring the need for empirical insights into tourist loyalty within heritage accommodations to support sustainability and cultural preservation. This study explores the influence of brand attributes and travel motivation on tourist loyalty, with service quality as a mediating factor, using Inna Group Bali’s heritage hotels as a case. A sequential mixed-methods approach was used, combining 400 survey responses analyzed through Structural Equation Modelling (SEM) with qualitative data from in-depth interviews. The results reveal that brand associations and pull motivation are key drivers of loyalty. Service quality fully mediates the effects of motivation and satisfaction. The proposed BHALIDEL model shows that combining architectural authenticity with modern service standards creates a competitive advantage. Recommendations include (1) partnering with heritage bodies to institutionalize conservation, (2) training staff in cultural intelligence, (3) curating thematic experiences with digital storytelling, and (4) applying adaptive reuse technologies to maintain heritage aesthetics while improving efficiency.